Pelatihan Pengelolaan Keuangan Pemuda Karang Taruna untuk Menunjang Usaha Produk Limbah Kulit Jok Di Desa Wanasalam Kabupaten Majalengka - Acep Komara; Enceng Yana; Sandi Nasrudin Wibowo (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Wanasalam Village is one of the villages in Majalengka Regency, West Java, with various potential resources. One of the resources owned by Wanasalam Village is the existence of youth organizations that are active in carrying out social and economic activities. One of the things the youth group works on in Wanasalam Village is the use of upholstery leather waste which is used to be processed into creative industrial products that have economic value. However, production activities carried out by Karang Taruna members have not optimally carried out bookkeeping or financial management so that they often experience problems in knowing the performance of economic activities carried out. Based on this, the community service team at Universitas Swadaya Gunung Jati conducted SME-based financial management training activities. Lecture methods, discussion methods and demonstrations are training methods used in community service activities. This service activity focuses on increasing knowledge and skills in managing finances for economic activities carried out. The result of this activity is that youth members are able to apply simple financial management to economic activities carried out by their organization.